Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10499-011-9481-5
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic activity of Bacillus subtilis in juvenile freshwater prawn, Macrobrachium rosenbergii (de Man) at different methods of administration to the feed

Abstract: This experiment was carried out to investigate the potential probiotic properties of Bacillus subtilis and suitable methods of administration to the commercial feed in juvenile Macrobrachium rosenbergii (de Man) from 25 August to 25 November 2008. Putative Bacillus subtilis bacterium isolated from juvenile M. rosenbergii intestine was added to commercial prawn feed as a probiotic. Five types of diets were prepared by mixing B. subtilis at level of 108 cells g -1 with commercial feed using different methods con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
5
23
1
2
Order By: Relevance
“…After 60 days of feeding, total bacterial count in water from each culture tank was 10 10 cells mL -1 , regardless of treatment. The same result was reported by Keysami et al (2012). The B. subtilis concentration increased to 10 8 -10 10 cells mL -1 in all treated tanks through the first 60 days, but was not found in the control tanks.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…After 60 days of feeding, total bacterial count in water from each culture tank was 10 10 cells mL -1 , regardless of treatment. The same result was reported by Keysami et al (2012). The B. subtilis concentration increased to 10 8 -10 10 cells mL -1 in all treated tanks through the first 60 days, but was not found in the control tanks.…”
Section: Discussionsupporting
confidence: 89%
“…The recent reports on the use of Bacillus spp. (Balcazar et al 2004;Salinas et al 2005;Keysami et al 2012) also demonstrated the beneficial effects of stimulating the growth improvements and gut immune system in the fish and prawn (Abraham et al 2008). After 60 days of feeding, total bacterial count in water from each culture tank was 10 10 cells mL -1 , regardless of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations